2017
DOI: 10.3390/md15020041
|View full text |Cite
|
Sign up to set email alerts
|

The Phytocomplex from Fucus vesiculosus and Ascophyllum nodosum Controls Postprandial Plasma Glucose Levels: An In Vitro and In Vivo Study in a Mouse Model of NASH

Abstract: Edible seaweeds have been consumed by Asian coastal communities since ancient times. Fucus vesiculosus and Ascophyllum nodosum extracts have been traditionally used for the treatment of obesity and several gastrointestinal diseases. We evaluated the ability of extracts obtained from these algae to inhibit the digestive enzymes α-amylase and α-glucosidase in vitro, and control postprandial plasma glucose levels in a mouse model of non-alcoholic steatohepatitis (NASH); a liver disease often preceding the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…The positive results on glycemic control observed in our study can be due to the inhibiting action of the polyphenolic composition (extracted from A. nodosum and F. vesiculosus) towards enzymatic activities, in an acarbose-like mechanism. The ability of a phytocomplex obtained from these algae to inhibit both enzymes has already been demonstrated by Roy et al (2011) and confirmed by Gabbia et al (2017) who showed that the administration of the extract in a diet particularly rich in fat in mice is associated with a delay in carbohydrate digestion but also with a decrease in its assimilation. Reducing PPG with the nutraceutical, probably, leads to a minor work for the β-cells and a consequent longer preservation of β-cell function.…”
Section: Ogtt Resultsmentioning
confidence: 69%
“…The positive results on glycemic control observed in our study can be due to the inhibiting action of the polyphenolic composition (extracted from A. nodosum and F. vesiculosus) towards enzymatic activities, in an acarbose-like mechanism. The ability of a phytocomplex obtained from these algae to inhibit both enzymes has already been demonstrated by Roy et al (2011) and confirmed by Gabbia et al (2017) who showed that the administration of the extract in a diet particularly rich in fat in mice is associated with a delay in carbohydrate digestion but also with a decrease in its assimilation. Reducing PPG with the nutraceutical, probably, leads to a minor work for the β-cells and a consequent longer preservation of β-cell function.…”
Section: Ogtt Resultsmentioning
confidence: 69%
“…Furthermore, Kellog et al (33), showed that the ethyl acetate fraction of Alaskan Fucus distichus, that also had the highest total phenolic content, had the highest α-glucosidase inhibitory effect. It was previously reported that fucoidan from F. vesiculosus and F. vesiculosus extract alone inhibited this enzyme (34,35). Su et al (36) have also shown that both saturated and unsaturated pure fatty acids inhibited α-glucosidase stronger than acarbose.…”
Section: Discussionmentioning
confidence: 84%
“…The in vivo anti-diabetic efficacy of seaweed has been shown in many animal studies (Gabbia et al 2017;Roy et al 2011;Song et al 2018;Zhao et al 2018). In human clinical trials, daily supplementation with Undaria pinnatifida and Sacchariza polyschides (as Gigantea bulbosa) balances blood glucose levels, decreases serum triglyceride concentrations, and increases high-density lipoprotein cholesterol in subjects with type 2 diabetes (Kim et al 2008).…”
Section: Type 2 Diabetesmentioning
confidence: 99%